Anti-p200 Pemphigoid: A Systematic Review - Kridin, Khalaf; Ahmed, A. Razzaque (Frontiers in Immunology, 2019)
The many clinical aspects of anti-p200 pemphigoid are not well characterized. We aimed to analyze and correlate known existing data on the epidemiological, clinical, histological, and immunological features of anti-p200 pemphigoid. We performed a review using Medline, Embase and Web of Science databases(1900-2018). Case reports and series of patients were included. Sixty-eight eligible studies comprising 113 anti-p200 pemphigoid patients were included in the qualitative analysis, with a mean age of onset of 65.5 years. All patients presented with bullae/vesicles, 54.3% had urticarial plaques. A similarity to bullous pemphigoid was reported in 66.1% of cases, but palmoplantar (51.4%), cephalic (40.3%) and mucosal (38.5%) involvement, besides frequent development of scars/milia (15.7%) were reported. Autoantibodies against recombinant laminin γ1 were detected in the sera of 73.1% of patients. Psoriasis was present in 28.3% of anti-p200 pemphigoid patients, particularly among Japanese patients (56.4%). The incidence of pustular psoriasis in this subgroup, was significantly greater than the normal population. In conclusion, the diagnosis of anti-p200 pemphigoid may be suspected when a subepidermal autoimmune blistering disease develops in a younger age group, with significant acral and cephalic distribution and mucosal involvement.